IMPLEMENTATION OF INTERNATIONAL NORMS AND PRACTICES IN INDONESIAN DIPLOMACY 1962-1969 IN MAINTAINING WEST IRIAN AS AN INSEPARABLE PART OF THE UNITARY STATE OF THE REPUBLIC OF INDONESIA - Rujito Dibyo Asmoro; Tahan Lumban Toruan; Syaiful Anwar; Luhut Simbolon (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
It can be said that issues about Papua that often come to the surface are always associated with the legal aspect of the entry of Papua into an inseparable part of the Unitary State of the Republic of Indonesia (NKRI). Groups that want Papua to be separated from the Unitary State of the Republic of Indonesia not only seek support from countries such as Solomon Island or Vanuatu but also voice it to the United Nations forum. In this regard, a historical reflection is needed to provide an overview with an academic approach regarding the validity of Indonesia's claim to the territory of Papua as an inseparable part of the Unitary State of the Republic of Indonesia. This study aims to determine international legal practices that are relevant to the legitimacy of West Irian being part of the territory of the Republic of Indonesia and Indonesia's diplomacy in international forums in defending Papua. This study uses a historical approach in the form of a systematic literature review through source collection and is interpreted to answer the focus of this research. The results showed that Indonesia's success in defending Papua after independence was influenced by mastery of the rules of international law, the spirit of struggle of Indonesian diplomats at that time, and international legal practices related to the right to be independent and free from colonialism